2023
DOI: 10.1111/gcb.16577
|View full text |Cite
|
Sign up to set email alerts
|

Are Mediterranean marine threatened species at high risk by climate change?

Abstract: Rapid anthropogenic climate change is driving threatened biodiversity one step closer to extinction. Effects on native biodiversity are determined by an interplay between species' exposure to climate change and their specific ecological and life‐history characteristics that render them even more susceptible. Impacts on biodiversity have already been reported, however, a systematic risk evaluation of threatened marine populations is lacking. Here, we employ a trait‐based approach to assess the risk of 90 threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Hence, reaching critical temperature thresholds will become increasingly frequent in the near future for many taxa, fostering redistributions, range shifts, and possibly triggering local extinctions (Chatzimentor et al, 2022). Our findings contribute to elucidate the mechanisms by which extreme climatic events can affect animal populations via a negative impact on reproduction.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Hence, reaching critical temperature thresholds will become increasingly frequent in the near future for many taxa, fostering redistributions, range shifts, and possibly triggering local extinctions (Chatzimentor et al, 2022). Our findings contribute to elucidate the mechanisms by which extreme climatic events can affect animal populations via a negative impact on reproduction.…”
Section: Discussionmentioning
confidence: 70%
“…This region has experienced a strong increment in the frequency and intensity of extreme heat events in recent decades (Díaz‐Poso et al, 2023; Kuglitsch et al, 2010; Serrano‐Notivoli et al, 2022) and it is expected to increase its maximum temperature extremes above the predicted global average (Seneviratne et al, 2016). Hence, reaching critical temperature thresholds will become increasingly frequent in the near future for many taxa, fostering redistributions, range shifts, and possibly triggering local extinctions (Chatzimentor et al, 2022). Our findings contribute to elucidate the mechanisms by which extreme climatic events can affect animal populations via a negative impact on reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean Sea is a hotspot of both biodiversity (Coll et al, 2010) and human uses and pressures (Coll et al, 2013;Micheli et al, 2013). It has suffered from overexploitation (Tsikliras et al, 2015), destructive fishing (Claudet and Fraschetti, 2010), marine pollution (Danovaro, 2003), including emerging pollutants such as marine litter (Anastasopoulou and Fortibuoni, 2019;Angiolillo and Fortibuoni, 2020;Fossi et al, 2020), global change (Chatzimentor et al, 2023), and invasive species (Tsirintanis et al, 2022). Various EU and regional environmental and conservation policies (e.g., MSFD, Habitats and Birds Directives, EU Biodiversity Strategy, Common Fisheries Policy, Barcelona Convention) aimed to safeguard Mediterranean Biodiversity and the sustainability of marine resources, with varying outcomes.…”
Section: Box 2 -The Mediterranean Sea Casementioning
confidence: 99%
“…The depletion of populations due to overfishing or overhunting has been identified or suspected as a major cause of the decline for many marine top predators (Pauly et al, 1998;Stevens et al, 2000;Myers and Worm, 2003;Lotze and Worm, 2009). A recent review of marine extinctions (Nikolaou and Katsanevakis, 2023) reported 8 cases of top predators' global extinctions (4 seabirds, 3 marine mammals, and 1 teleost fish) and 89 cases of local extinctions; the main driver of extinction of top predators was human-induced direct mortality (i.e., overexploitation and bycatch).…”
Section: The Human Factor In Marine Top Predators Declinementioning
confidence: 99%
“…The latter includes animal care practices on land for both young and adult individuals with specific medical and targeted nutritional care. M. monachus has been recently recognized as one of the Mediterranean marine mammals’ species and a highly vulnerable and high-climate-risk species ( 28 ), and this might impose additional burden on the animal’s care efforts in the future.…”
Section: Introductionmentioning
confidence: 99%